The Effect Of Health Education Using Leaflet Media On The Level Of Knowledge About Menstrual Hygiene In Adolescents At PP An-Najiyah 1 Jombang - Nikmah Tutimatus Sholihah; Tiara Fatma P; Dina Camelia; Yuyud Wahyudi (International Journal of Health Engineering and Technology, 2025)
The natural process that occurs in adolescent girls every month is menstruation. Lack of knowledge regarding hygiene practices during menstruation can cause various infections, including reproductive tract infections. Providing health education using leaflet media is considered one of the media that is quite effective media in increasing adolescent knowledge. This study aims to determine the effect of health education using leaflet media on the level of knowledge about menstrual hygiene in adolescents at PP An-Najiyah 1 Jombang. The research design used was an analytic pre-experimental design with a one-group pretest-posttest approach. The population in this study were adolescents in classes I, II, and III of MTS, totalling 47 adolescents. Sampling using purposive sampling with a total of 25 respondents. The research instrument used was a knowledge questionnaire, then analyzed using the Wilcoxon test. The results of the study before the intervention most adolescents had sufficient knowledge, as many as 15 respondents (60%), and after being given the intervention, almost all adolescents had good knowledge, as many as 20 respondents (80%). Wilcoxon test results obtained a p value = 0.000 <0.005, then H1 is accepted. This study concludes that there is an effect of health education using leaflet media on the level of knowledge about menstrual hygiene in adolescents at PP An-Najiyah 1 Jombang. It is hoped that future researchers can develop more varied educational media, and the number of samples is expanded so that the results of research are more representative.